2016
DOI: 10.3945/ajcn.116.133892
|View full text |Cite|
|
Sign up to set email alerts
|

A vegetable, fruit, and white rice dietary pattern during pregnancy is associated with a lower risk of preterm birth and larger birth size in a multiethnic Asian cohort: the Growing Up in Singapore Towards healthy Outcomes (GUSTO) cohort study

Abstract: The VFR pattern is associated with a lower incidence of preterm birth and with larger birth size in an Asian population. The findings related to larger birth size warrant further confirmation in independent studies. This trial was registered at clinicaltrials.gov as NCT01174875.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
95
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(102 citation statements)
references
References 43 publications
(66 reference statements)
6
95
1
Order By: Relevance
“…However, sensitivity analyses in participants who completed a 3-d food diary produced similar estimates, albeit wider CIs (but not with abdominal adiposity measures, which might be due to the reduced sample size). In addition, we also showed that our 24-h recall is moderately valid and has good reproducibility in previously published results (27,29,30,52,62). Second, maternal diet was only assessed during 26-28 wk of gestation, which may not be representative of a diet followed throughout pregnancy.…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…However, sensitivity analyses in participants who completed a 3-d food diary produced similar estimates, albeit wider CIs (but not with abdominal adiposity measures, which might be due to the reduced sample size). In addition, we also showed that our 24-h recall is moderately valid and has good reproducibility in previously published results (27,29,30,52,62). Second, maternal diet was only assessed during 26-28 wk of gestation, which may not be representative of a diet followed throughout pregnancy.…”
Section: Discussionmentioning
confidence: 73%
“…The clinic staff also guided the participants on completing food diaries at home for the following week. Nutrient analysis of the dietary records was performed by using nutrient analysis software (Dietplan; Forestfield Software Ltd.) containing a food-composition database of locally available foods (29), with modifications made for inaccuracies found.…”
Section: Diet Quality Assessmentmentioning
confidence: 99%
“…dietary patterns) underlying food consumption ( 25 , 31 , 32 ) . A total of five factors were determined in this study, and the number of factors retained was based on the eigenvalue, factor interpretability after varimax rotation and a scree plot showing the proportion of the variance of total consumption of the food variables ( 15 , 25 , 33 ) . The dietary pattern score for each participant was calculated by summing the standardised frequency of food groups weighted by their factor loadings.…”
Section: Methodsmentioning
confidence: 99%
“…In the present review, the definition of SGA varied from birth weight < 2•5th percentile (23) to < 5th percentile (32,40,41) to <10th percentile of gestational age (34,35,38) . The majority of studies (seventeen articles) defined SGA as birth weight below the 10th percentile for the gestational age.…”
Section: Study Characteristicsmentioning
confidence: 99%